2022
DOI: 10.1002/adtp.202200076
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stem Cells Promoting Spinal Cord Injury Repair Visually Monitored by AIE‐Tat Nanoparticles

Abstract: Spinal cord injury (SCI) is a severe body trauma that can cause permanent loss of somatic nerve function and lacks effective treatment. Transplantation of stem cells is a promising therapeutic approach for SCI but faces with the difficulty of long‐term tracking of stem cells in vivo precisely. Herein, this work wishes to report a kind of umbilical cord mesenchymal stem cells (UC‐MSCs) labeled with aggregation‐induced emission (AIE)‐Tat nanoparticles (NPs) for tracing the repair and treatment of SCI. These AIE‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…7 b) [ 121 ]. Similarly, Xie et al reported that transplantation of umbilical cord MSCs could effectively promote SCI repair [ 125 ]. Yao et al fabricated microfibers of 3D MSCs through electrospinning in spun cell cultures to mimic neural tissues and facilitate their integration with host tissues.…”
Section: Treatment Strategies For Spinal Cord Injurymentioning
confidence: 99%
“…7 b) [ 121 ]. Similarly, Xie et al reported that transplantation of umbilical cord MSCs could effectively promote SCI repair [ 125 ]. Yao et al fabricated microfibers of 3D MSCs through electrospinning in spun cell cultures to mimic neural tissues and facilitate their integration with host tissues.…”
Section: Treatment Strategies For Spinal Cord Injurymentioning
confidence: 99%
“…The results showed no adverse effects as well as SCI recovery showed by histopathological and behavioral rehabilitation results. Moreover, the cells were able to conserve the cell viability in microenvironments with highly reactive oxygen species and produce nerve growth factors [ 132 ].…”
Section: Introductionmentioning
confidence: 99%